ANALISIS KONSUMEN DALAM MELAKUKAN KEPUTUSAN PENGGUNAAN JASA INDIHOME DI KOTA KENDARI - Titop, Herman; Zainuddin, Muh Zabir; Suharlian, Suharlian; Suharndoyo, Suharndoyo (Fakultas Ekonomi Dan Bisnis Universitas Sulawesi Tenggara, 2022)
The development of technology in the modern era, especially information technology, makes people easily find information very quickly, both containing positive and negative elements. With internet access within the household, it is definitely very supportive of work to access information, one solution to overcome this is by subscribing to internet without a quota as the primary connection and mobile internet as a secondary connection. This study aims to 1) determine the influence of consumers in deciding to use Indihome services in Kendari City, and 2) determine the variables that have a dominant influence on consumer decisions in deciding to use Indihome services in Kendari City. The research method used is field research (field studies). The sample in this study was taken using the Judgment sampling method and the determination of the number of samples using the population proportion estimation method and the convident level used was 95% so that the number of samples was 100 people. Statistical test using multiple linear regression analysis. Data collection techniques were carried out by questionnaires, observations, and interviews. The results showed that 1) partially the product quality variable (X1) had a positive and significant effect on the decision to use Indihome products (Y); 2) the price variable (X2) has a positive and significant effect on the decision to use Indihome products (Y); 3) the distribution variable does not have a significant influence on the decision to use Indihome products (Y); 4) the promotion variable does not have a significant influence on the decision to use Indihome products (Y); 5) based on the results of the simultaneous test analysis (F test) it is known that the consumer behavior variables consisting of, product quality (X1), price (X2), distribution (X3), and promotion (X4) together (simultaneously) have an effect on on the decision to use Indihome products in Kendari City (Y); and 6. the product quality variable is the variable that has the strongest influence on the decision to use Indihome PT. Telkom Indonesia Tbk. Kendari.